MODEL PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS APPSGYAER.COM UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA PELAJARAN IPA KELAS V(LIMA) DI MI DARUL ULUM WIDANG TUBAN - Haris, Ahmad; ., Winnuly (-, 2025)
The aim of this research is to produce learning media that is suitable and practical for use by students and teachers. This research method is R&D (Research and Development) and was developed using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) research model. The research subjects were class V students at MI Darul Ulum Widang. Testing the suitability of this media was carried out by material experts, media experts, science teachers at MI Darul Ulum Widang, and the results of validation by supervisors with percentages of 80%, 91.6%, 94%, 94% respectively, with the category "Very Appropriate", "Very Practical", and "Very Good", then the percentage of student interest respondents was 66.67% with the category "Very Interested", and 33.34% with the category "Interest", then from the results of the post-test and pre-test students experience improvement after using learning media applications. From the results of this research, it can be said that the application media is feasible and very practical and is also of interest to students to be used as a science learning media to get to know the parts and functions of plants.